Potensi Daya Hambat Ekstrak Caulerpa lentillifera terhadap Mikroba yang Diisolasi dari Penyakit Luka dari Lele - Renanda Baghaz Dzulhamdhani Surya Putra; Muhammad Arifin Gymnastyar; Yanu Iswahfiudin; Asus Maizar Suryanto Hertika (Jurnal Perikanan Pantura (JPP), 2024)
Caulerpa lentillifera is known to have an antibacterial benefit based on various research findings. The study aims to analyze the potential of the Caulerpa lentillifera water extract in the bacterial barrier power isolated from the lele infected wound disease. The methods carried out included extracting Caulerpa lentillifera water extract. The study was conducted using an experimental method with a Complete Random Scheme (RAL) consisting of control, 50 mg/l and 100 mg/ l on each extract. The results showed that the water extract of Caulerpa lentillifera showed significant increases in the barrier strength at doses of 50 mg / l and 100mg/l with diameters of 7.8 mm and 8.4 mm respectively in bacteria isolated from the disease-affected fish wounds. On the other hand, on the result of the bacterial barrier that is isolated from the living media, the lele obtains a low barrier. This is due to the bioactive activity of the antibacterial water extract Cauleroa lentillifera specific to bacteria. It can be concluded that Caulerpa lentillifera is also capable of inhibiting the growth of the bacteria causing the lily's wound